Hunting stability and derailment analysis of the high-speed railway vehicle moving on curved tracks. (9th September 2019) - Uyulan, Caglar; Gokasan, Metin; Bogosyan, Seta
An advanced train model, which examines hunting instability and derailment in one integrated model implicitly is presented. In terms of a control subject, proposed model is compatible with nonlinear controllers to stabilise hunting oscillations and perform real-time derailment avoidance. The dynamical model, which consists of a vehicle body, two bogie frames, and two wheelsets in each bogie frame was modelled with 35-DOF. Heuristic nonlinear creep model and flange-rail contact model were used to reveal the effects of the creep forces and moments. The eigenvalues at the hunting speed were calculated by the assistance of the Gershgorin disc theorem. The vehicle speed influence on evaluated derailment quotient was investigated at a sharp radius of the curved track. Safe speeds were also estimated via active derailment criteria. The main superiority of the proposed model is that one can both predict incipient derailment actively and also determine nonlinear critical hunting speeds with higher precision.